Effect of Duty Cycle on the Lifetime of Single Crystal LiNi0.5Mn0.3Co0.2O2/Graphite Lithium-Ion Cells. Issue 13 (1st October 2020) - Cheng, J. H.; Harlow, J. E.; Johnson, M. B.; Gauthier, Roby; Dahn, J. R.
Abstract : The effects of different duty cycles, involving mixtures of charge-discharge cycling and open-circuit storage segments, on the lifetime of single crystal NMC532/graphite cells were studied. Charge-discharge cycling was performed at C/3 with open circuit storage times of 0, 12, 84, 180 h or 3 months applied at upper cutoff voltages (UCV) of 4.1, 4.2 and 4.3 V. Testing was made at 40 °C for a period of 2.5 years. Cells tested to the same UCV showed similar capacity loss and impedance growth with time, independent of the ratio between the time spent cycling or in storage. Differential voltage analysis showed that the vast majority of the capacity loss stemmed from lithium inventory loss at the negative electrode with little or no loss of active materials. The thickness of the pouch cells after testing increased with the fraction of time spent cycling and the amount of gas generated in the cells increased with fraction of time spent in storage at the UCV. These results show that cycled and stored cells age differently, even though a similar capacity fade rate was observed in the first 2.5 years of cell life, which may cause different failure modes at the end of cell life.